CAD Model Details via Curved Knot Lines and Truncated Powers. (February 2022) - Sabin, Malcolm A.; Fellows, Chris; Kosinka, Jiří
Abstract: This paper describes a method for adding surface details to existing CAD models. Our approach is based on truncated powers, which allows us to align the added details with curved knot lines on the surface. Additionally, (truncated) powers give us precise control over the continuity of the perturbed surface across the (curved) knot lines. Our representation is compatible with current CAD/CAM practise and standards, and we showcase it on several examples. Highlights: A method for adding surface details to existing CAD models. Based on curved knot lines via truncated powers. Precise control over continuity across (curved) knot lines.